2007
DOI: 10.1038/sj.ijo.0803713
|View full text |Cite
|
Sign up to set email alerts
|

Components of the metabolic syndrome and colorectal cancer risk; a prospective study

Abstract: Objective: To examine the relation of well-known factors of the metabolic syndrome (MetS) as well as related circulating factors, with risk of colorectal cancer. Methods: We performed a case control study of 306 colorectal cancer cases and 595 matched controls nested in the Northern Sweden Health and Disease Cohort. Levels of C-peptide, glycated haemoglobin (HbA1c), leptin and adiponectin were measured in cryopreserved samples. Body mass index (BMI), systolic and diastolic blood pressure and fasting and post-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
110
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(123 citation statements)
references
References 43 publications
(57 reference statements)
7
110
0
2
Order By: Relevance
“…Norway was not included in the current study because blood samples were only recently collected and very few colorectal cancer cases have occurred after blood donation. Sweden was not included because an independent study of HbA1c and colorectal cancer risk has already been undertaken (15).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Norway was not included in the current study because blood samples were only recently collected and very few colorectal cancer cases have occurred after blood donation. Sweden was not included because an independent study of HbA1c and colorectal cancer risk has already been undertaken (15).…”
Section: Methodsmentioning
confidence: 99%
“…A study based on Swedish populations showed a direct association of HbA1c with colorectal cancer risk only at very high concentrations (top decile levels; ref. 15). Most of these studies had a relatively small sample size (between 67 and 380 case subjects); thus, only a few studies allowed investigation into the role of HbA1c in colon and rectal cancers separately (15,22,23), and when this was the case, sample size and statistical power were generally limited.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tamakoshi et al (2005) reported that invasiveness of CRC in women is associated with a high level of leptin in serum. It is suggested that only very high levels of leptin and other metabolic factors acting simultaneously (levels of C-peptide, HbA1c, and leptin/ObR ratio) activate and increase CRC proliferation (Stocks et al, 2008).…”
Section: Obesity-leptin and Adiponectinmentioning
confidence: 99%